The effectiveness of levosimendan in newborns with low cardiac output syndrome in the multiple organ dysfunction - A. V. Golomidov; O. G. Kryuchkova; E. V. Grigoriev; V. G. Moses; K. B. Moses (Вестник анестезиологии и реаниматологии)
Introduction. The combination of multiple organ dysfunction syndrome and low cardiac output syndrome (MODS + LCOS) is an unfavorable phenotype of a critical condition with a high risk of death, in which standard cardiotonic therapy is not always effective.The objective was to evaluate the effectiveness of levosimendan in the treatment of small cardiac output syndrome in newborns with multiple organ dysfunction syndrome. Materials and methods. 68 newborns with MODS+ LCOS were studied using the continuous method. All the studied children were on artificial lung ventilation, received inotropic therapy, were rated on the NEOMOD scale of 2 points or more, and had a reduced cardiac output fraction rate (< 60%) in Echocardiography. All patients were randomly assigned to two groups: group A (n = 34) received levosimendan for standard inotropic therapy (adrenaline, norepinephrine, dopamine in any combination). Levosimendan was added at the start of inotropic therapy at a dosage of 0.05–0.1 micrograms/kg–1/min–1 and was used until hemodynamic stabilization. Group B received standard inotropic therapy without levosimendan. Results. Primary treatment outcomes: mortality was 2.9% in group A and 5.8% in group B, respectively, p = 0.5. Secondary treatment outcomes: neurological complications were detected in 5.8% in group A and 29.4% in group B, respectively, p = 0.01; persistent multiple organ failure developed in 2.9% and 17.6%, respectively, p = 0.046; the duration of hospitalization was 24 (20;29) days and 46 (40;48) days, respectively, p = 0.001; duration of hospitalization in Intensive Care Unit was 10 (8;13) days and 20 (18;26) days, respectively, p = 0.001; duration of MODS was 7 (6;8) days and 8 (7;9) days, respectively, p = 0.272; duration of mechanical ventilation of the lungs was 8 (6;8) days and 9 (7;10) days, respectively, p = 0.346; duration of cardiotonic support was 8 (6;8) days and 7 (7;8) days, respectively, p = 0.212.Conclusion. Addition of levosimendan to inotropic therapy in newborns with MODS+ LCOS reduces the risk of neurological complications, the incidence of persistent multiple organ failure, and reduces the duration of hospitalization in general and directly in the emergency department.